The advent of non-thermal, non-tumescent techniques for treatment of varicose veins. (February 2016) - Bootun, Roshan; Lane, Tristan RA; Davies, Alun H
Varicose veins are common and their management has undergone a number of changes over the years. Surgery has been the traditional treatment option, but towards the 21st century, new endovenous thermal ablation techniques, namely, radiofrequency ablation and endovenous laser ablation, were introduced which have revolutionised the way varicose veins are treated. These minimally invasive techniques are associated with earlier return to normal activity and less pain, as well as enabling procedures to be carried out as day cases. They are, however, also known to cause a number of side-effects and involve infiltration of tumescent fluid which can cause discomfort. Non-thermal, non-tumescent methods are believed to be the answer to these unwelcome effects. Ultrasound-guided foam sclerotherapy is one such non-thermal, non-tumescent method and, despite a possible lower occlusion, has been shown to improve the quality of life of patients. The early results of two recently launched non-thermal, non-tumescent methods, mechanochemical ablation and cyanoacrylate glue, are promising and are discussed.